2011
DOI: 10.1007/s00264-011-1389-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage posterior instrumentation and anterior debridement for active tuberculosis of the thoracic and lumbar spine with kyphotic deformity

Abstract: Objective The purpose of this study was to validate the efficacy and safety of single-stage posterior instrumentation and anterior debridement for treatment of active spinal tuberculosis with kyphotic deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 28 publications
0
26
1
1
Order By: Relevance
“…Following the advent of modern spinal instrumentation systems, several authors have reported combined anterior and posterior fusion either as a single-stage or as a twostage procedure following the initial description of the procedure by Yau et al [12][13][14][15][16][17][18][19][20][21][22][23] in 1974. Earlier apprehensions regarding the use of metal implants in the presence of active tubercular infection were overcome following the realization that tubercle bacilli had slow rates of division, lower bacillary counts than pyogenic infections, and do not produce adhesion molecule and bio-film [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Following the advent of modern spinal instrumentation systems, several authors have reported combined anterior and posterior fusion either as a single-stage or as a twostage procedure following the initial description of the procedure by Yau et al [12][13][14][15][16][17][18][19][20][21][22][23] in 1974. Earlier apprehensions regarding the use of metal implants in the presence of active tubercular infection were overcome following the realization that tubercle bacilli had slow rates of division, lower bacillary counts than pyogenic infections, and do not produce adhesion molecule and bio-film [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has high infection resolution rates, ability to eradicate paravertebral abscess and achieve vertebral fusion in 97% of cases [2]. Additionally, surgery has the advantage to control spinal deformity and limits or improves the neurological injury resulting from this disease [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the study by Moon et al (11), we excluded patients with severe kyphosis to make the baseline of patients more similar to yield a more accurate comparison between surgery and nonsurgery groups. Even after TB was cured by chemotherapy, kyphosis could progress, and it could lead to delayed paralysis for patients treated conservatively (16,18). Jain and Jain (8) also concluded that panvertebral disease and long-segment disease including kyphosis correction should be indications for instrumented stabilization.…”
Section: Prognostic Factorsmentioning
confidence: 96%